2021
DOI: 10.3390/jtaer16040064
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategic Marketing Management Model for the Specificities of E-Commerce in the Supply Chain

Abstract: The study seeks to answer the question of what strategic directions and opportunities we have for business in the midst of the info-communication changes of our time. In this research, we compare the results of non-representative primary research (cluster analysis and discriminant analysis) with the factors and latest methods of e-commerce or even mobile commerce and traditional commerce and their main differences. Based on the four clusters examined, we develop a new strategic model for practice with suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…The lower these are, the more compatible the product or application (with previous settings and/or behavior) is perceived, which (theoretically) is always positively related to the level of acceptance [115]. Therefore, the empirical review of the influence on acceptance is primarily carried out from the perspective of perceived compatibility and is considered at various points in the context of TAM research [116][117][118][119][120].…”
Section: Customizationmentioning
confidence: 99%
“…The lower these are, the more compatible the product or application (with previous settings and/or behavior) is perceived, which (theoretically) is always positively related to the level of acceptance [115]. Therefore, the empirical review of the influence on acceptance is primarily carried out from the perspective of perceived compatibility and is considered at various points in the context of TAM research [116][117][118][119][120].…”
Section: Customizationmentioning
confidence: 99%
“…This trend has been confirmed by various studies explaining that co-creation positively influences buying intention in specific contexts such as online communities [64] and luxury brands [65]. It has been reported that purchasers co-creating a new product tend to boost their emotional involvement [66] by releasing knowledge, offering feedback, and helping each other, which can make them important for the company [67,68]. When consumers are engaged in the company and in the production process, they can be advocates and come up with solutions for problems in a product.…”
Section: Value Co-creation Behavior and Cpbmentioning
confidence: 65%
“…Social network analysis in symbiosis system focuses on functional entities and how entities are connected. For instance, Gyenge et al [ 20 ] proposes a brand-new marketing strategy model in international e-commerce suppling chain, indicating that enterprises could reach their market goals through effective and delivered communication, and fulfil the integral market needs. This method is discussed in terms of the network density, network centrality, network sub-group, and small world characteristic in analysing the characteristics of industrial symbiosis [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This method is discussed in terms of the network density, network centrality, network sub-group, and small world characteristic in analysing the characteristics of industrial symbiosis [ 18 ]. Schiller proposed a complexity-derived approach for Social-Material Network Analyses of industrial networks [ 20 ]. The social relations of making contact in a matchmaking marketplace is also researched, through investigating a new Australian industrial symbiosis network case and the social relations of inter-organization contact, as a precursor to a waste transfer in an industrial symbiosis matchmaking market [ 21 ].…”
Section: Literature Reviewmentioning
confidence: 99%